Influence of design parameters on the performance of slotted Savonius hydrokinetic turbine - Rishabh Kumar; Anuj Kumar (Results in Engineering)
The main objective of this study is to optimize the performance of slotted Savonius hydrokinetic turbine by investigating the effects of blade profile (semi-circular, elliptical, Benesh, NACA6409), number of blades (2–4), overlap ratio (0.05–0.20), gap ratio (0.0–0.25), and Reynolds number (0.76 × 105 – 3.02 × 105). This study employed a numerical approach with SST k-ω turbulence model to investigate the performance. To validate the numerical results, experiments have also been carried out at constant Reynolds number of 1.51 × 105. This study determined the optimal geometrical configuration for the slotted Savonius hydrokinetic turbine to be a two-bladed design with a NACA6409 profile, an overlap ratio of 0.10, and a zero-gap ratio. The optimized turbine configuration exhibited a consistent increase in maximum power coefficient with increasing Reynolds number at a tip speed ratio of 0.9. The optimal combination yielded a maximum power coefficient of 0.3784 at tip speed ratio of 0.9, at Reynolds number of 3.02 × 105. Furthermore, a correlation for the power coefficient of a Savonius hydrokinetic turbine with NACA 6409 blades has been developed based on numerical data, considering parameters such as number of blades, overlap ratio, gap ratio, Reynolds number, and tip speed ratio.